Conjugation of antibody fragments to ferritin protein cage for targeted delivery to cancer cells. - Thinzar Win. (2012)
Ferritin is engineered as a targeted carrier for therapeutic and diagnostic agents. It is a naturally occurring biomaterial and functions in iron homeostasis in various organisms. The ferritin in this study is a protein cage derived from an archaeon Archaeoglobus fulgidus with unique self-assembling properties and remarkable heat stability. Due to its proteinaceous nature, the A. fulgidus ferritin (AfFtn) contains readily available reactive moiety for functionalization with targeting ligands. In this study, we have coupled mutant A. fulgidus ferritin (AfFtn-AA) with single-chain variable fragment (scFv) antibody to the surface of the protein cage for targeting purpose.